Independent relationship between 24-hour blood pressure and carotid intima-media thickness - Metsing, Lebogang Stanley (My University, 2013)
Introduction: The changing socio-economic landscape in Africa has brought with it unique health challenges previously uncommon in people of African ancestry. Noncommunicable diseases such as coronary artery disease and stroke have emerged as pressing public health concern highlighting the need to find more on-target diagnostic tools as well as therapeutic interventions. Although ambulatory blood pressure (AMBP) has in many studies conducted in the western world proved to be an independent predictor of carotid intima-media thickness (C-IMT), such results cannot outright be imputed to people of African ancestry living in Africa. That is because people of African ancestry living in Africa are not only of a different ethnicity but are still in the early phases of an epidemiological transition while people in the western countries who are mostly Caucasians, are believed to be in the middle to late phases of an epidemiological transition. Methods: The relationship between the intima-media thickness of the common carotid artery (SonoCalcTM IMT version 3.4) and AMBP (Space labs model 90207) was determined in 320 randomly selected participants of African descent living in an urban developing community in South Africa. Relationships were determined after adjustment for (clinic blood pressure) BPc, age, gender, alcohol and tobacco use, the presence or absence of diabetes mellitus or inappropriate blood glucose control measured by glycated hemoglobin (ghb), antihypertensive therapy and menopausal status. III Results: Mean age for the study population was 43.7± 16.0 years. Both BPc and AMBP parameters were strongly associated with C-IMT (p<0.001) in univariate analysis. In multivariate analysis with BPc. and AMBP entered into separate models and after adjusting for cofounders, BPc. and AMBP maintained significant associations with CIMT. [BPc (partial r=0.0648, p< 0.1612), systolic blood pressure 24 (SBP24) (partial r= 0.236, p< 0.001), systolic blood pressure day (SBPd) (partial r= 0.302, p<0.05), systolic blood pressure night (SBPn) (partial r= 0.0983, p<0.05)]. When adjustments were made with BPc. and SBP24 entered into the same model, BPc lost its association with C-IMT, [SBP24 (partial r=0.236, p<0.001) SBPd (partial r=0.149, p<0.05), SBPn (partial r=0.172, p<0.05)]. Importantly the relationship between SBP24 and C-IMT persisted independent of body mass index (BMI), BPc and age. SBP24 had the highest significant association with C-IMT. Conclusion: SBP24 independently predicts C-IMT even in a model that includes conventional systolic blood pressure (SBPc) leading to the conclusion that AMBP is a more effective tool at diagnosing C-IMT alterations while BPcdoes not have an independent relationship C-IMT.
Dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand in fulfillment of the Master of Science in Medicine in the School of Physiology
Keywords: Chronic Disease; Blood Pressure Monitoring, Ambulatory; Carotid Intima-Media Thickness